2001
DOI: 10.1128/aem.67.3.1351-1362.2001
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Activity Dynamics of Nitrifying Bacteria in a Phosphate-Removing Biofilm

Abstract: The microbial community structure and activity dynamics of a phosphate-removing biofilm from a sequencing batch biofilm reactor were investigated with special focus on the nitrifying community. O 2 , NO 2 ؊ , and NO 3 ؊ profiles in the biofilm were measured with microsensors at various times during the nonaerated-aerated reactor cycle. In the aeration period, nitrification was oxygen limited and restricted to the first 200 m at the biofilm surface. Additionally, a delayed onset of nitrification after the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
4
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 290 publications
(203 citation statements)
references
References 61 publications
14
182
4
3
Order By: Relevance
“…In contrast to the aerobic incubation experiments, no uptake of organic or inorganic carbon sources by Nitrospira-like bacteria was observed in the absence of oxygen. However, combined FISH and microsensor measurements revealed that high numbers of Nitrospira-like bacterial cells can persist in biofilm zones with low oxygen pressure (17,36,41). The ability to switch from aerobic respiration to an anaerobic metabolism should be advantageous in such habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the aerobic incubation experiments, no uptake of organic or inorganic carbon sources by Nitrospira-like bacteria was observed in the absence of oxygen. However, combined FISH and microsensor measurements revealed that high numbers of Nitrospira-like bacterial cells can persist in biofilm zones with low oxygen pressure (17,36,41). The ability to switch from aerobic respiration to an anaerobic metabolism should be advantageous in such habitats.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years, the gene encoding the active site subunit of amoA has been exploited increasingly as a marker molecule for AOB diversity research in natural and engineered systems (Baribeau et al, 2000;Gieseke et al, 2001;Horz et al, 2000;Rotthauwe et al, 1997). Initially, amoA gene fragment sequences published previously of Nitrosospira spp.…”
Section: Aob Phylogeny Inferred From Amoamentioning
confidence: 99%
“…Nitrosomonas europaea, Nitrosomonas eutropha, Nitrosomonas halophila Juretschko et al (1998) NOLI 191 Nitrosomonas oligotropha lineage Gieseke et al (2001) Nso 1225 Ammonia oxidizing Beta-proteobacteria Mobarry et al (1996) Nso 190 Ammonia oxidizing Beta-proteobacteria Mobarry et al (1996) Neu 653 Nitrosomonads (halotolerant and obligatehalophilic) (applied with NEU653comp) Wagner et al (1995) NmV Nitrosoccus mobilis Juretschko et al (1998) Nsv 443 Nitrosospira, Nitrosolobus, Nitrosovibrio Mobarry et al (1996) Ntspa 712…”
Section: Ammonia Oxidizersmentioning
confidence: 99%